Spurious "Examples" of Ancient Dental Implants or Appliances: Part Two of a Series - Marshall Joseph Becker (Dental Anthropology Association, 1994)
In addition to the various copies of ancient dental appliances, enormous numbers of reports deal with fanciful and unverifiable examples. These spurious dental bridges (or fake ancient crowns, inlays, or fillings) have been traced to their sources. While most of these spurious examples, such as the "stone" implant from Turkey (Atilla, 1993), discussed below, are found in the secondary literature, a few are accepted by scholars who were well versed in ancient dentistry (Guerini, 1909:68, n1). In most cases, these spurious examples are the result of wishful thinking combined with poor referencing of earlier secondary sources, ignorance of the technology involved in the construction of dental appliances, and a lack of scholarly communication.